ANALYSIS OF PROFESSIONAL ACCOUNTANTS ETHICAL CODE IN INDONESIA FROM AL QURAN PERSPECTIVE - Kartini, Tina; Sholihati, Ghina Mar'atu (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The rise of cases of accountants who do not comply with the standards of professional accountants' code of ethics and the need for an Islamic code of ethics which is considered important for Islamic accountants. Islamic accountants must adhere to the Islamic values-based code of ethics which is currently not compiled by the Institute of Indonesia Chartered Accountants(IAI). This study aims to determine the Code of Ethics of Professional Accountants in Indonesia from the Al Qur'an Perspective. This study uses a qualitative method with a descriptive approach. The sample used is a social situation which consists of threeelements: place, actor, and activity. From the results of this study, it can be concluded that there are five professional accountants' codes of ethics, namely: integrity, objectivity, competence and professional prudence, confidentiality, and professional behavior. The five codes of ethics are in line with the code of ethics contained in the Qur'an, which is honest and loves truth, fairness, learning the lawful, trustworthy, and disciplined.